Selected Least Studied but not Forgotten Bioluminescent Systems1. (22nd February 2017) - Oba, Yuichi; Stevani, Cassius V.; Oliveira, Anderson G.; Tsarkova, Aleksandra S.; Chepurnykh, Tatiana V.; Yampolsky, Ilia V.
Abstract: Bioluminescence is a form of chemiluminescence generated by luminous organisms. Luminous taxa have currently been reported from about 800 genera and probably over 10 000 species in the world. On the other hand, their bioluminescent systems, including chemical structures of luciferins/chromophores and the genes encoding luciferases/photoproteins, have been elucidated from only a few taxonomic groups, for example beetles, bacteria, dinoflagellates, ostracods and some cnidarians. Research efforts to understand unknown bioluminescence systems are being conducted around the world, and recently, for example, novel luciferin structures of luminous enchytraeid potworms and fungi were identified by the authors. In this study, we review the current status and perspectives, in the context of postgenomic era, of most likely novel but less‐revealed bioluminescence systems of ten selected organisms: earthworm, parchment tubeworm, fireworm, scaleworm, limpet, millipede, brittle star, acorn worms, tunicate and shark, which indeed are the next focus of our international collaboration. Abstract : Bioluminescent organisms are found in 800 genera of 13 phyla and 4 kingdoms of Life. They use ~50 distinct independently evolved bioluminescence systems comprising different chemical components: luciferin–luciferase pairs or photoproteins. Currently, the chemical structures of these components are known for only nine bioluminescence systems. Here, we review the current status and perspectives, in the context of postgenomic era, of novel bioluminescence systems of 10 selected organisms under study by the international collaborative project led by the authors: earthworm, parchment tubeworm, fireworm, scaleworm, limpet, millipede, brittle star, acorn worms, tunicate and shark.